Formación docente e investigación educativa: paneles de especialistas de líneas de investigación - Rossi, Beatríz; Álvarez, Mary; Vittarelli, Marcelo; Montañez, Silvia; Silva, Myriam; Campos, Mónica; Ávila Paz, Cecilia; Tallone, Alicia; Pruzzo de Di Pego, Vilma; Bellavida, Elizabeth; Porta, Luis; Díaz Gómez, María Cristina; et al. (Anuario Digital de Investigación Educativa, 2019)
Ninguno